Ngữ nghĩa của dữ liệu trong cơ sở dữ liệu với thông tin không đầy đủ - Hồ, Nguyễn Cát; Thăng, Lê Thế (Journal of Computer Science and Cybernetics, 2016)
In this paper, we consider semantics of data in databases with incomplete information as a pair S=(r, a), where r is a relation with null values and a is an assignment of every tupe t in r to a set of objects in the real world. Some relationships between a database and the real world are also examined.